2018
DOI: 10.1111/aji.12973
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of platelet‐to‐lymphocyte ratio in women with preeclampsia

Abstract: The PLR is an easily accessible and cost-effective parameter, which may be used as a more useful marker for prediction of PE compared to platelet indices. Our study showed that PLR can serve as a useful diagnostic marker of PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 36 publications
6
38
0
1
Order By: Relevance
“…PLR has been shown to increase significantly in many inflammatory diseases (11,(13)(14)(15). Consistent with the literature, in our study, PLR was found to be significantly higher in patients with PID, whereas sensitivity (68%) and specificity (60%) of PLR were lower than NLR and WBC, and higher than MPV and PDW.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…PLR has been shown to increase significantly in many inflammatory diseases (11,(13)(14)(15). Consistent with the literature, in our study, PLR was found to be significantly higher in patients with PID, whereas sensitivity (68%) and specificity (60%) of PLR were lower than NLR and WBC, and higher than MPV and PDW.…”
Section: Discussionsupporting
confidence: 91%
“…MPV, which is a marker of function and activation of platelets, is altered by platelet activation (12,13). MPV has been shown to decrease in inflammatory diseases such as rheumatoid arthritis and inflammatory bowel disease in recent studies (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Their deuterogenic parameters, such as NLR, LMR and PLR, were considered as the inflammation-related indicators with respect to predict many diseases, including pregnancy complications [22,23]. Several studies, sample size ranging from 107-814, suggested that maternal NLR/PLR was positive associated with severe pre-eclampsia/gestational diabetes mellitus/acute appendicitis during pregnancy [24,25,26]. However, some considered that NLR/PLR has no significant association with gestational diabetes mellitus and HELLP syndrome [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Other hematological and radiological variables studied along with PLT indices in preeclampsia have validated the use of MPV to prognosticate the disease progression. [192021] A study done by Kim et al . showed that PLT-lymphocyte ratio predicted a shorter time interval between admission and delivery of the preeclampsia cases.…”
Section: Discussionmentioning
confidence: 99%